球面圆线定位提高工件圆度的分析研究 - 刘楠嶓; 腾瑛瑶; 王伟; 陈兴洲 (Jixie chuandong)
By designing rational motion parameter and dimension parameter between spherical surface and taper surface and using the characteristic of self-orientation of circularity of spherical surface, the centerline of two circularities of spherical surface, instead of the conventional centerline of taper surface is used to improve the roundness of high precision-grinding.